The White Van Syndrome: Fear, Trauma and the Culture of Intimidation in Sri Lanka - Nechikkottil Radhakrishnan, Swapna; Farooqui, Abida (Journal of Education Culture and Society, 2025)
Aim. The research paper examines how ordinary objects, like white vans during the Sri Lankan Tamil conflict, undergo a transformation in meaning, becoming symbols of fear through their association with illegal abductions. These objects, once neutral, take on a sinister role, spreading terror within vulnerable groups, particularly the Tamil minority. The study highlights the psychological and social impacts of this shift in perception, where fear permeates not only the immediate victims but also the broader community, creating an atmosphere of mistrust and anxiety. The white vans thus became a powerful motif of terror during the conflict. Method. The paper uses the theory of classical conditioning as the methodological framework for analysing trauma responses. Specifically, it will explore how neutral environmental stimuli like a white van become associated with traumatic experiences, leading to the continuous perception of threat. Result. The study found that fear is created within human being through associations. The association of white van to a fear eliciting object in the conflict zones of Sri Lanka derives as it was used for illegal disappearances. Conclusion. Analysing the psyche of characters in the novels Sugandhi Alias Andal Devanayaki (Ramakrishnan 2018), Island of A Thousand Mirrors (Munaweera, 2016) and the documentary White Van Stories (Manimekalai, 2015), the paper states how white vans became synonymous with terror, intimidation and trauma in the Sri Lankan psyche. These vehicles became synonymous with illegal abductions, deeply embedding fear in the national psyche, regardless of their actual use, perpetuating a collective trauma.